Aggressive Versus Moderate Fluid Replacement for Acute Pancreatitis: An Updated Systematic Review and Meta‐Analysis - Muhammad Ehsan; Aamna Badar Ahmad; Haseeba Javed; Afra Zahid; Hafiz Sheheryar Aamir; Huzaifa Ahmad Cheema; Muhammad Ayyan; Biah Mustafa; Abia Shahid; Muhammad Abdullah Ilyas; Kamal Kandel; Rehmat Ullah Awan; et al. (JGH Open)
ABSTRACT Background A conservative strategy is the primary modality of treatment for acute pancreatitis of which fluid replacement is an important component. Since the results regarding early aggressive versus moderate fluid replenishment for acute pancreatitis are inconsistent, we sought to compare outcomes between the two resuscitation strategies in our meta‐analysis. Methods We searched MEDLINE (PubMed), Embase, the Cochrane Library, and ClinicalTrials.gov for all available randomized controlled trials (RCTs) assessing outcomes for patients treated with aggressive fluid replacement compared to moderate fluid replacement. Our primary outcome was all‐cause mortality. Results Our meta‐analysis included 6 RCTs involving a total of 632 patients. Our results showed that aggressive fluid resuscitation increased the risk of all‐cause mortality as compared to moderate fluid replacement (RR 2.40, CI: 1.38–4.19). For all of our secondary outcomes which included the development of organ failure, severe pancreatitis, pancreatic necrosis, clinical improvement, development of SIRS, persistent SIRS, and length of hospital stay, the results indicate that there was no significant difference between the two groups. Conclusions Aggressive fluid resuscitation is associated with higher mortality as compared to moderate fluid replacement in patients with acute pancreatitis. RCTs with larger sample sizes are needed to provide greater statistical power and establish more definitive conclusions.